Evolutionary conservation of Trichomonas-mycoplasma symbiosis across the host species barrier - Bailey, Nicholas P.; Shao, Yuxin; Du, Shaodua; Foster, Peter G.; Fettweis, Jennifer; Hall, Neil; Wang, Zheng; Hirt, Robert P. (Frontiers in Microbiology, 2023)
The protozoan parasite Trichomonas vaginalis is the most common cellular sexually transmitted disease in humans, and the closely related species Trichomonas gallinae is an avian parasite of ecological and economic importance. Phylogenetic evidence suggests T. vaginalis arose during bird to human transmission of a T. gallinae-like ancestor. T. vaginalis shares a strong clinical association with the independent sexually transmitted pathogen Metamycoplasma (formerly Mycoplasma) hominis, and the uncultured bacterium "Candidatus Malacoplasma (formerly Mycoplasma) girerdii", with the latter association being an order of magnitude stronger. Both bacterial species have been shown to profoundly influence T. vaginalis growth, energy production and virulence-associated mechanisms.Methods: Evidence for a novel Malacoplasma sp. was discovered by in vivo Illumina metatranscriptomics sequencing of the T. gallinae-infected pigeon mouth. We leveraged published 16S rDNA profiling data from digestive tract of 12 healthy and 24 T. gallinae-infected pigeons to investigate association between the novel Malacoplasma sp. and T. gallinae. We utilised Illumina metagenomics sequencing targeted to pigeon oral and crop samples infected with the novel Malacoplasma sp. to generate its full-length genome sequence. Sequence similarity network analysis was used to compare annotated proteins from the novel Malacoplasma sp. with a range of other related species.Results: Here we present evidence for a novel Malacoplasma species, related to "Ca. M. girerdii", that is strongly associated with T. gallinae in the upper digestive tract of domestic pigeons. Analysis of the genome sequence revealed gene features apparently specific to a Trichomonas-symbiotic Malacoplasma lineage.Discussion: These data support a model of long-term association between Trichomonas and Malacoplasma spp. that has been conserved across diversification of the Trichomonas lineage and the host species barrier from birds to human.